1999
DOI: 10.1523/jneurosci.19-12-05034.1999
|View full text |Cite
|
Sign up to set email alerts
|

Depression Duration But Not Age Predicts Hippocampal Volume Loss in Medically Healthy Women with Recurrent Major Depression

Abstract: This study takes advantage of continuing advances in the precision of magnetic resonance imaging (MRI) to quantify hippocampal volumes in a series of human subjects with a history of depression compared with controls. We sought to test the hypothesis that both age and duration of past depression would be inversely and independently correlated with hippocampal volume. A sample of 24 women ranging in age from 23 to 86 years with a history of recurrent major depression, but no medical comorbidity, and 24 case-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
724
13
40

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,231 publications
(819 citation statements)
references
References 61 publications
42
724
13
40
Order By: Relevance
“…These results can be interpreted according to the two most prevalent hypotheses, the toxic stress, and the dementia prodrome. According to the toxic-stress hypothesis of depression, high levels of glucocorticoids (McEwen, 1997;Sapolsky, 1993) induce shrinking of the highly sensitive hippocampal gray matter (Sapolsky et al, 1985;Sheline et al, 1999;Steffens et al, 2000;Videbech and Ravnkilde, 2004). According to the prodromal dementia hypothesis of LLD, a subgroup of subjects develops LLD as a very early clinical presentation of dementia (Alexopoulos et al, 1993;O'Brien et al, 2004;Steffens et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These results can be interpreted according to the two most prevalent hypotheses, the toxic stress, and the dementia prodrome. According to the toxic-stress hypothesis of depression, high levels of glucocorticoids (McEwen, 1997;Sapolsky, 1993) induce shrinking of the highly sensitive hippocampal gray matter (Sapolsky et al, 1985;Sheline et al, 1999;Steffens et al, 2000;Videbech and Ravnkilde, 2004). According to the prodromal dementia hypothesis of LLD, a subgroup of subjects develops LLD as a very early clinical presentation of dementia (Alexopoulos et al, 1993;O'Brien et al, 2004;Steffens et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies have reported a small but significant reduction in the volume of hippocampus in patients with depression or post-traumatic stress disorder. [81][82][83] Atrophy and decreased functions of the hippocampus could explain the reduction, observed in depressed patients, in negative feedback control that this brain region exerts on the hypothalamic-pituitary-adrenal axis. 84 Other studies have shown decreased plasma levels of BDNF in patients with major depression 15 and increased BDNF level in hippocampus in postmortem tissue from patients treated with antidepressant drugs.…”
Section: Bdnf and Depressionmentioning
confidence: 99%
“…Two groups found significant reductions in grey matter volume in the subgenual prefrontal cortex in family history-positive subjects, suggesting that studying more homogenous patient groups may result in more consistent findings as further studies emerge. 203,204 Some of the changes may constitute primary biological traits associated with the risk of developing mood disorder, while others may represent sequelae of the illness and its burden 205 or treatment effects. 195 Primary changes that could be used as endophenotypes should be detectable in a proportion of unaffected relatives, but such studies are less common.…”
Section: Brain Imaging and Endophenotypesmentioning
confidence: 99%